HUKUM ASTROFOTOGRAFI DALAM RUKYATUL HILAL PENDEKATAN FIKIH KONTEMPORER - Ramadhani, M.; Amir , Rahma (HISABUNA: Jurnal Ilmu Falak, 2025)
The main problem of this research is how is the law of astrophotography in rukyatul hilal using the contemporary fiqh approach? The main problem is then broken down into several sub-problems or research questions, namely: 1) What is the mechanism of Astrophotography in Rukyatul hilal?, 2) What are the views of classical and contemporary Ulama in Rukyatul Hilal. This type of research is classified as qualitative. The author specifically uses a sharia and astronomical approach. The data sources used are: primary data comes directly from data sources that are collected and related to the object of research while secondary data comes from scientific works related to the object of the problem being studied, to analyze the data used qualitative analysis techniques. The results of this study show differences of opinion regarding the views of classical and contemporary scholars. The views of classical scholars in the mazhab of fiqh such as the Syafi'i school of thought, for example Imam Nawawi in Al-Majmu' emphasized that Rukyatul Hilal is done with the eyes, not through or other tools. In the Syafi'i school of thought, one just person is enough to state that he has seen the hilal to determine the beginning of the Hijri month. The views of contemporary scholars such as Ahmad Rofiq added that Rukyatul Hilal is an instrument to implement the command to see the hilal based on the rukyat hadith. In order for someone to see the hilal, binoculars or other technology are used to reduce obstacles or difficulties. The implications of this study are that every study is expected to contribute to the problems studied and can be recommended to related parties for development. The presence of this article is expected to the government to provide a container or study related to the law of astrophotography in rukyatul hilal with a contemporary fiqh approach. In addition, it is expected that the full role of the younger generation will continue to study various fiqh studies related to matters related to worship.